Performance of TialN coated carbide tool in peck drilling stainless steel SS316L with pressurized minimum quantity lubrication - M., Malik; R., Sharif; S., Sharif; Wan Azhar, Wan Yusoff (AENSI Publishing, 2014)
Austenitic stainless steel, SS316L is vastly being used in food and medical applications instead of titanium alloys especially in the third world countries. The presence of chromium in SS316L improves its scratch-resistance and corrosion resistance while the nickel content provides a smooth and polished finish. The molybdenum element’s enhances the hardness of the SS316L and ensure the sharpness of the cutting edge whereby these properties are very crucial in orthopedic devices. Machining of austenite stainless steel is considered difficult due its unfavorable properties such as gummy, high strength, high modulus of elasticity, low thermal conductivity and high work hardening. The contradiction between policy maker and industrialist in reducing pollution during machining can be compromised by using the Pressure Minimum Quantity Lubrication (PMQL). This technique of cooling and lubricating is applied and evaluated during peck drilling of SS316L with the combination of pressurized lubrication oil spray to the tool and work piece interface. This paper presents an experimental investigation on the performance of CVD-TiAlN coated carbide drills when drilling austenite stainless steel SS316L at various cutting speeds of 110, 130 and 150m/min with feed rates of 0.05, 0.1 and 0.15mm/rev, at customized point angles 110, 122.5 and 135 degree on fixed 12 degree rake angle and 30 degree helix angle. Surface finish, tool failure modes and tool life were evaluated at various conditions to determine the optimum condition of the process. It was found that point angle and the interaction of cutting speed and feed rate are the pronounced effect on the tool performance. Result also showed that feed rate was the dominant factor affecting the surface roughness.